Medical students’ perception of online learning during the COVID-19 pandemic: a cross-sectional study in Nepalgunj Medical College - Dhami, Dabal Bahadur (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: The COVID-19 pandemic compelled educational institutions worldwide to rapidly adopt online learning, causing significant disruption to traditional medical education. This study aimed to assess medical students’ perceptions of online learning during the pandemic at Nepalgunj Medical College.Methods: A cross-sectional descriptive study was conducted using a self-administered questionnaire among undergraduate students who attended online classes between March 2020 and September 2021. A total of 150 students participated.Results: Most respondents (76%) were aged 18–24 years, and 85% reported having good IT skills. Flexibility emerged as the most significant advantage of online learning, reported by 92% followed by the ability to stay at home (80%) and easy access to study materials (73%). Conversely, the lack of interaction with educators and peers was identified as the major disadvantage by 82% of students, with 68% reporting technical difficulties. When comparing learning modalities, face-to-face teaching was perceived as significantly more effective in achieving learning objectives than online learning (p < 0.001). Students also reported higher engagement and activity levels in traditional classroom sessions compared to online classes. Despite these limitations, overall acceptance of online learning was high, with a mean Likert score of 3.8/5.Conclusion: Online learning played a vital role in sustaining medical education during the COVID-19 pandemic. While it cannot fully replace face-to-face teaching, a blended learning approach combining online and traditional methods may enhance learning outcomes, engagement, and adaptability in medical education.